A Note on Chromy's Sampling Procedure. (5th November 2020) - Chauvet, Guillaume
Abstract: Chromy (1979) proposed an unequal probability sampling algorithm, which is the default sequential method used in the SURVEYSELECT procedure of the SAS software. In this article, we demonstrate that Chromy sampling is equivalent to pivotal sampling. This makes it possible to estimate the variance unbiasedly for the randomized version of the method programmed in the SURVEYSELECT procedure.